Global simulation of an RF Czochralski furnace during different stages of germanium single crystal growth, part II: to investigate the effect of the crucible's relative position against the RF coil on the isotherms, flow fields and thermo-elastic stresses. Issue 3 (5th January 2017) - Honarmandnia, M.; Tavakoli, M. H.; Sadeghi, H.
Abstract : By changing the vertical relative position of the crucible against the induction coil, flow and thermal fields in the germanium melt are seriously affected. Abstract : By changing the vertical relative position of the crucible against the induction coil, the flow and thermal fields in the melt are seriously affected. The distribution of heat generation along the crucible vertical inner wall is assumed in three cases. A downward shift of the crucible leads to an increase in the heat generation rate near the crucible rim and its reduction near the bottom, while the temperature distribution along the crucible bottom wall varies monotonically with the transmission of the crucible. With downward movement of the crucible and relocation of the hottest region from bottom to top, a reduction in the maximum temperature of 17 degrees can be seen and the freezing amount of liquid on the floor rapidly increased. In contrast, if the crucible is pulled upward, the crucible vertical wall's temperature decreases from bottom to top, due to heat generation by the induced electromagnetic field, and some melt was frozen at the melt free surface. Also, there were two eddy currents in opposite directions within the melt which improve the heat transfer to the crystal–melt interface and the convexity of the germanium crystal decreased. Changes in the manner of thermo-elastic stress distribution against the crucible's relative movement have also been reported.